Konsep Manusia dalam Tafsir Al-Mishbah Karya Muhammad Quraish Shihab dan Relevansinya dengan Projek Penguatan Profil Pancasila dan Profil Pelajar Rahmatan Lil Alamin (Prosiding Keislaman dan Sains, 2025)
Allah, the Almighty, has created mankind in the best way possible. In both physical and non-physical forms, humans are superior to any other creature. As a consequence of this perfection of creation, human beings are given a special mandate by Allah Subḥānahu wa ta'āla, namely as khalīfah and 'abdun. In order for this khalīfah and 'abdun mandate to run properly and not run off the rails that have been outlined by the laws of Allah, the Almighty, humans were given special provisions. This special provision can be called human excellence, commonly termed fiṭrah. Ironically, in everyday life, we often encounter cases that are inversely proportional to the privileges possessed by humans themselves. The privileges possessed by humans are not used according to what they should be. So that there are often disputes, hostility, and other negative things by those who are intelligent and intelligent. Of course, this human privilege will be more meaningful and valuable if it is used for positive things. One of the positive things in question is to be used in the realization and success of the independent curriculum program, especially in the Pancasila Student Profile Strengthening Project and the Rahmatan lil Alamin Student Profile (P5P2RA). The research method that the author uses is a qualitative method, which is more descriptive research, the data collected is in the form of words or images, so it does not emphasize numbers, with the type of library research, precisely in the group of revelation text studies. The author finds the concept of man in the interpretation of Al-Mishbah surah Al-Baqarah verses 30-39, namely; man is 1) a creature that has the ability to think, 2) a creative creature, 3) an independent creature, 4) a creature that likes to work together, and 5) a believing creature. This is very closely related to P5P2RA which has six dimensions, namely; faith, devotion to God Almighty, and noble character, global diversity, mutual cooperation, independence, critical reasoning, and creativity. From the author's findings above, it can be concluded that the human concept in the interpretation of Al-Mishbah surah Al-Baqarah verses 30-39 is very relevant to P5P2RA. This is evident from the six dimensions of P5P2RA, there are five dimensions in the human concept above, namely; 1) faith, piety to God Almighty, and noble character, 2) mutual cooperation, 3) independence, 4) critical reasoning, and 5) creativity.
Keywords: Humans; Tafsir Al Misbah; P5P2RA